EDITORIAL COMMENTS ON THE ARTICLE OF D.S. KRIVONOSOV ET AL "OPTIMIZATION OF THE TREATMENT OF ELDERLY PATIENTS WITH MYOCARDIAL INFARCTION BY REVASCULARIZATION IN COMBINATION WITH INOTROPIC STIMULATION AND MYOCARDIAL UNLOADING" - статья Редакционная (Столичная издательская компания, 2016)
.